The effect of age-related sensorimotor changes on step-down strategy: a predictive simulation study - Schreff, Lucas; Waterval, Niels F. J.; van der Krogt, Marjolein M.; Häufle, Daniel F. B.; Müller, Roy (Scientific reports, 2025)
Humans adjust neuromuscular control in anticipation of a step-down during walking. Due to age-related sensorimotor changes, older adults may require adaptation of this control to step-down safely. We used predictive simulations to investigate how muscle weakness and delayed neural transmission affect anticipatory control during step-down. Five model variants were developed: a default model, two with muscle strength reduced to 80% and 60%, and two with neural delays increased by 20% and 40%. For each model, we tested two strategies in the trailing leg during the last contact before step-down: reduced soleus activity (SOL strategy) and increased hamstring activity (HAM strategy). We systematically varied step-down height and anticipatory control levels. For the SOL strategy, both muscle weakness and neural delay reduced the maximum feasible step-down height, with muscle weakness requiring more precise adjustments. The HAM strategy was mainly affected by neural delay and showed less sensitivity to control precision. While the SOL strategy generally performed better, the HAM strategy was more robust under severe weakness. These results suggest that the HAM strategy may benefit individuals with progressive sensorimotor decline, while maintaining SOL strategy applicability - e.g., through strength training - could help maintain its benefits. Further investigations are needed to confirm this.
Veröffentlicht: 21. August 2025
Gesehen am 20.01.2026